3D Simulation of Vibrating Diamond Grinding - Grabchenko, Anatoly; Fedorovich, Vladimir; Pyzhov, Ivan; Kundrak, Janos (Manufacturing Technology Journal, 2014)
A method of 3D simulation of vibrating diamond-abrasive machining based on a finite element model of the process is worked out. Calculation of the deflected mode of grinding area is the evidence that high-frequency vibration has a considerable effect on the amount of fractured material. Equivalent stress in the grinding zone increases up to 1.5-2.0 times. By means of FEM simulation of ultrasonically assisted grinding it is found that when grinding without imposing high frequency vibrations the maximum load is concentrated on a certain face of diamond grain. This can lead to the fracture of a grain in contact area with a bond and subsequent untimely shedding of the grain from the bond. However, uniform distribution of the stresses along the grain when imposing high-frequency vibrations improves retention of the grain in bond.
Keywords: 3D simulation; finite element model; diamond grinding wheel; vibrating diamond-abrasive machining